PROSPEK USAHA INOVASI PRODUK KAPSUL BAWANG HITAM SEBAGAI SUMBER ANTIOKSIDAN PENANGKAL RADIKAL DALAM MENGHADAPI PANDEMI - Utami, Ratih Apri; Anarofida, Anarofida; Pratiwi, Meihilda Dona; Purborini, Ajeng Gendis; Putri, Dhea Karunia; Annisa, Rofiu Sisil (Politeknik Negeri Semarang, 2023)
In the era of the Covid-19 pandemic, an immune booster is really needed which can make a person's immune system more immune to the corona virus. Therefore, the product